FIGURAÇÕES DA MORTE EM HOMERO E PLATÃO - Magdaleno, Adriana Soares (2020)
This article presents the representation of death by means of two distinct voices of Greek culture: Homer and Plato. In Homer we can see the death of heroic warrior. Plato searches for the behavior of the ideal citizen though the Socrates' death. The aim of this work is to present the death as a cultural phenomenon, where each society has regular symbols.